2020
DOI: 10.1021/acs.jpcc.0c03297
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Correlated Ion Dynamics in Plastic Ionic Crystals and Polymerized Ionic Liquids

Abstract: Understanding the mechanisms controlling ionic conductivity is critical for the development of the next generation of batteries and supercapacitors. This paper discusses the significant role played by ionic correlations in conductivity of concentrated ionic systems. Our studies of an organic ionic plastic crystal reveal that correlations in ions dynamics suppress conductivity by 25–100 times in comparison to the expected uncorrelated ionic conductivity estimated from the Nernst–Einstein relationship. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 49 publications
1
52
1
Order By: Relevance
“…One should note, however, that for various liquids, especially the so-called fragile glass formers, deviations from the Stokes-Einstein, Debye-Stokes-Einstein, and Nernst-Einstein relations were reported. 26,[28][29][30][31] Different explanations were proposed, e.g., in terms of the heterogeneity of glassy dynamics 26,29,30 or within other models. 32,33 Correspondingly, translationrotation coupling and decoupling also are long-standing topics in the physics of glass-forming liquids.…”
Section: Revealed a Closementioning
confidence: 99%
See 1 more Smart Citation
“…One should note, however, that for various liquids, especially the so-called fragile glass formers, deviations from the Stokes-Einstein, Debye-Stokes-Einstein, and Nernst-Einstein relations were reported. 26,[28][29][30][31] Different explanations were proposed, e.g., in terms of the heterogeneity of glassy dynamics 26,29,30 or within other models. 32,33 Correspondingly, translationrotation coupling and decoupling also are long-standing topics in the physics of glass-forming liquids.…”
Section: Revealed a Closementioning
confidence: 99%
“…One should note, however, that for various liquids, especially socalled fragile glass formers, deviations from the Stokes-Einstein, Debye-Stokes-Einstein, and Nernst-Einstein relations were reported. 25,27,28,29,30 Different explanations were proposed, e.g., in terms of the heterogeneity of glassy dynamics 25,28,29 or within other models. 31,32 It is obvious that a comparison of the temperaturedependent reorientational relaxation time (T) and of the dc conductivity  dc (T) with the viscosity (T) should help clarifying the mechanism of the rotation-translation coupling found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to D , one must consider the degree of uncorrelated ion motion H R –1 , as poor salt dissociation (low salt solubility) can lead to strong correlations and reduce overall conductivity. In fact, our recent work shows that H R –1 , while often close to 1 at high ion concentrations, can significantly change from low to moderate ion concentrations . To maintain sufficient salt solubility, polymers with relatively high dielectric constants (ϵ r ) such as poly­(ethylene oxide) (PEO; ϵ r = 7.5) or poly­(oligo­(oxyethylene) methacrylate) (ϵ r = 6) are most widely used. …”
Section: Introductionmentioning
confidence: 99%
“…It is challenging to design systems with optimized λ + , because these various important factors are interconnected in a complex way. ,,, In searching for systems with better performance than PEO, there has been significant recent interest in developing polymer backbones with various polarities and chemistries. ,,, Meanwhile, previous works have also shown that changing the sizes of cations and anions can significantly impact conductivity in polymer systems. ,,, In particular, a variety of lithium salts with anions of various sizes, , as well as salts of a few other metals, , have been explored recently.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Sokolov and coworkers provided with useful insights regarding ionic correlations in polyIL electrolytes. [ 58 ] Their in‐depth analysis showed that ionic correlations play a significant role in Li + transport, and the same charge correlations (cation–cation or anion–anion) are the major mechanism suppressing the ionic conductivity. They also suggest that such “negative” correlations can be turned to the “positive” one (i.e, enhancing ionic conductivity) through structuring ion‐lattice interactions such as 1D percolating ion channels, emphasizing the structural design of polymer electrolytes.…”
Section: Well‐defined Polymer Matricesmentioning
confidence: 99%